Stitching the Strip: 7 Visions for the Future of Southeast Coralville - Aleman, Marcos; Baker, Logan; Barragree, Joshua; Belanger, Blake; Benyshek, Julie; Chen, Si; Cooke, Shelby; Cross, Rachel; Dirks, Harrison; Dunay, Morgan; Gray, Allyssa; Hahn, Howard; et al. (Kansas State University. College of Architecture, Planning & Design, Department of Landscape Architecture and Regional & Community Planning, 2018)
The Strip in Coralville is iconic of mid-century American strip retail development. Highway 6, also known as 2nd Street, is a 5-lane arterial street with the highest volume of traffic in the metro area. Buildings are located far from the street edge, and the vast majority of the area is covered with paved parking lots. While 2nd Street’s sidewalks are adequately wide and established street trees provide shade and enclosure, there are few crosswalks, creating unsafe conditions for pedestrians crossing the street. The Southeast Commercial District, located at the intersection of 2nd Street and 1st Avenue, is comprised of multi-family residential housing, retail, commercial, and industrial uses. Many of the buildings are functionally obsolete and some parcels exhibit evidence of neglect. Creative planning and design proposals envision alternative futures for the district, but existing conditions present several significant challenges. Towering electrical transmission lines bisect the district, some parcels are known to be contaminated and others potentially contaminated, and all new inhabited structures must be elevated above the FEMA 100-year flood plain to be insurable. At the same time, some conditions present opportunities: The Clear Creek and Iowa River waterfronts are underutilized and two rail lines with public transit potential bookend the district, and with any urban design proposal, there are opportunities for creating a sense of identify and place. Stitching The Strip: 7 Visions for the Future of Southeast Coralville presents urban design ideas for the Southeast Commercial District in Coralville, Iowa. Twenty-three mid-level landscape architecture graduate students enrolled in an intensive 8-week Community Planning and Design studio completed the work during the summer of 2018. The studio was co-led by Associate Professor Blake Belanger and Associate Professor Howard Hahn. The effort was supported with funding from Kansas State University’s Technical Assistance to Brownfields (TAB), and would not have been possible without support and engagement from Maggie Egbarts, TAB Services Coordinator (EPA Regions 5 and 7). We are also grateful for the support and guidance from Dan Holderness, Coralville City Engineer and Scott Larson, Coralville Assistant City Engineer, as well as our visiting design critic Associate Professor Carl Smith who delivered both exceptional insights and humor. The idea for the collaboration emerged from discussions at the 2017 National Brownfields Training Conference in Pittsburgh. Goals of the collaborative service-learning studio included providing students with first-hand experience working with a community, generating creative ideas for advancing the dialogue about planning the future of southeast Coralville, engaging residents and stakeholders and responding to their input, and supporting the mission of the project partners. The studio’s process included rigorous mapping of various conditions, a community planning workshop, design development through an iterative process, a final presentation to project partners and the Coralville Community Advisory Panel, and a public open house exhibiting posters of student proposals. In Chapter 1, we introduce Coralville’s Southeast Commercial District and present eight influential site and contextual factors identified in our research. We detail the studio’s methods and process, and introduce the seven student design proposals. In the following seven chapters, we present specific urban design strategies for establishing a new mixed-use district. In contrast to a singular master plan, the collection of ideas presented in Stitching The Strip provides a multitude of ideas that can be compared, evaluated, prioritized, and perhaps hybridized. We aspire that Stitching The Strip will contribute to the ongoing dialogue about the future of the Southeast Commercial District, and serve as an enduring legacy project for Coralville.
Keywords: Landscape architecture; Urban design; Brownfield reuse redevelopment; Transit-oriented development; Kansas State University; Technical Assistance Brownfields